Volume 4: Codes, Standards, Licensing and Regulatory Issues; Student Paper Competition 2009
DOI: 10.1115/icone17-75990
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Aspects for Uranium Carbide and Uranium Dicarbide Fuels in Supercritical Water-Cooled Nuclear Reactors

Abstract: SuperCritical Water-cooled Reactors (SCWRs) are a Generation IV nuclear reactor concept. Two main SCWR design concepts are Pressure-Vessel (PV) type and Pressure-Tube (PT) type reactors. SCWRs would use light-water coolant at operating parameters set above the critical point of water (22.1 MPa and 374°C). A reason for moving from current Nuclear Power Plant (NPP) designs to SCW NPP designs is that a SCW NPP will have a thermal efficiency of 45 to 50%, a remarkable improvement from the current 30–35%. SCWRs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Currently, UO 2 has been used in Light Water Reactors (LWRs) and Pressurized Heavy Water Reactors (PHWRs); however, it has a low thermal conductivity which may result in high fuel centerline temperatures. Previous studies Pioro et al, 2010;Villamere et al, 2009) have shown that the fuel centerline temperatures could exceed the industry limit of 1850°C (Reisch, 2009) when UO 2 is used at SCWR conditions. These studies have been conducted based on an average thermal power per channel and have not taken into account the effects of fuel-sheath gap on the sheath and fuel centreline temperatures.…”
Section: Fig 1 Schematic Diagram Of Pv Scwr (Us Doe 2002)mentioning
confidence: 99%
“…Currently, UO 2 has been used in Light Water Reactors (LWRs) and Pressurized Heavy Water Reactors (PHWRs); however, it has a low thermal conductivity which may result in high fuel centerline temperatures. Previous studies Pioro et al, 2010;Villamere et al, 2009) have shown that the fuel centerline temperatures could exceed the industry limit of 1850°C (Reisch, 2009) when UO 2 is used at SCWR conditions. These studies have been conducted based on an average thermal power per channel and have not taken into account the effects of fuel-sheath gap on the sheath and fuel centreline temperatures.…”
Section: Fig 1 Schematic Diagram Of Pv Scwr (Us Doe 2002)mentioning
confidence: 99%